Nghiên cứu bào chế Hydrogel chứa tiểu phân Niosome Tadalafil / Nguyễn Ngọc Chiến, Phạm Thị Mai Anh - Nguyễn, Ngọc Chiến
Tadalafil loaded niosomes were formed by ethanol injection method. Suspension were prepared with tadalafil as the core, span 60 and cholesterol as coating materials and D-α-tocopheryl polyethylene glycol 1000 succinate (TPGS) as stabilizer. The oil phase containing Span 60, cholesterol and tadalafil was injected into a solution of TPGS 0.2% as the water phase by a high speed mixer at 300 rpm for 2 minutes at 650C. The obtained suspensions were stirred at 150 rpm for 1 hr to evaporate ethanol. The final hydogels were achieved by dispersion of xanthan gum and a permeability enhancer into the tadalafil niosomes. The drug release of the formulated hydrogels reached up to 21.11 ± 0.40% after 6 hours as measured with Franz diffusion cells.